Thermodynamic balancing of heat and mass transfer process to minimize its entropy generation by mass injection and extraction. (November 2020) - Chen, Junjie; Han, Dong; He, Weifeng
Highlights: Integrated mathematical models for counter-flow heat and mass transfer process are built. Thermodynamic balancing of simultaneous heat and mass transfer process is accomplished by water mass injection/extraction. The total entropy generation can be minimized at the balance conditions of HCR = 1. A minimum value of NEG = 0.0054 is obtained at the inlet relative humidity of 0.85. Adjusting the injection height shows significant potential in reducing the total entropy generation, although the HCR is always 1. Abstract: In this paper, a specific procedure is considered to reveal how the simultaneous heat and mass transfer process achieves thermodynamic balancing such that the total entropy generation can be minimized, in combination with the unsaturated state of inlet humid air. In view of the simultaneous heat and mass exchange with zero and single water mass injection/extraction, integrated mathematical models based on mass and energy conservation are established using the finite difference method. The novel proposed driving force criterions, heat transfer temperature difference (HTTD) and mass transfer pressure difference (MTPD), are balanced at off-design conditions, while the relevant influences from the critical parameters are investigated and analyzed. The simulation results demonstrate that the total normalized entropy generation (NEG) can be minimized at the balance condition of HCR = 1, meanwhile, the energy efficiency has a minimum value. It is found that single mass injection can better decrease the entropy generation at its minimum point and along the variation curve, compared to zero and single mass extraction. Specific injection ratio is given at the balance condition with fixed inlet liquid-gas ratio. Moreover, it is valuably observed that varying the injection height shows significant potential in reducing entropy generation, although the HCR keeps a constant value of one. Furthermore, a minimum value of NEG = 0.0054 is emerged at φi  = 0.85, as raising the relative humidity of inlet humid air can effectively reduce the total entropy generation and elevate the energy efficiency, simultaneously. Graphical abstract: Image, graphical abstract